Lucas (1972): A personal view from the wrong side of the subsequent fifty years - David E. W. Laidler (The University of Western Ontario, Department of Economics, 2021)
Lucas (1972) was a paper that permanently changed the course of macroeconomics, even though its "money supply surprise" model lost its central place in the area within a decade because of empirical difficulties. However, Lucas's novel methodology, based on clearing markets and rational expectations, still dominates orthodox macroeconomic theorising. An unfortunate side effect of this has been that, because mainstream models have no analytic room for money to play a key role in economic activity, the theoretical case for taking that role seriously was undermined just at the time when traditional monetarist macro-models were facing empirical problems. The consequences of all this for today's monetary policy environment are briefly discussed.
Keywords: E13; E31; E40; E52; N01; 330; Lucas; neutral money; monetarism; Keynesianism; micro-foundations; clearingmarkets; inflation; recession